Uso de anestésicos no local da inserção do Trocater em cirurgia de Histerectomia Videolaparoscópica e seu efeito analgésico no pós operatório: uma revisão sistemática e meta-análise - Bárbara Silva Nogueira (2023)
Introduction: Managing postoperative pain is a challenge in surgery. In laparoscopic hysterectomies for benign conditions, pain can significantly impact postoperative recovery. The ERAS (Enhanced Recovery After Surgery) protocol is a set of practices aimed at improving postoperative recovery and reducing complications after surgeries. It recommends the infiltration of local anesthetics at the trocar insertion site for minimally invasive gynecological surgery. However, the effectiveness of this procedure in relieving postoperative pain still requires robust evidence. Objective: Analyze recent studies on postoperative pain after laparoscopic hysterectomy associated with local anesthesia at the trocar insertion site. Methodology: A systematic review following the PRISMA Statement for Reporting Systematic Reviews and Meta-analyses standards. PubMed/MedLine, Web of Science, and Scopus databases were used. PROSPERO registration: CRD42022371268. Results: 483 studies on the topic were identified. After screening, three studies were selected, totaling data from 136 patients. Findings showed that pain was reduced in the first (MD= -1.63 [-2,16, -1,09]) and second hour (MD= -1,68 [-2,18, -1,17]) after laparoscopic hysterectomy due to the injection of analgesics at the trocar insertion site. Conclusion: In the analyzed studies, the infusion of anesthetic substances at the incision site for trocar insertion in laparoscopic hysterectomy presented a local analgesic effect, especially in the early postoperative hours. Further high-quality, randomized, controlled studies across multiple centers are needed to robustly demonstrate the efficacy of this anesthetic practice.